Konstanta laju pengeringan daun sambiloto menggunakan pengering tekanan rendah - Sri Rahayoe; Budi Rahardjo; Rr. Siti Kusumandari (Jurnal Rekayasa Proses, 2008)
Herbs (traditional medicine) such as sambiloto leaves are senisitive to heat, therefore the drying process of herbs were performed at low-pressure. At low pressure, evaporation of water in the herbs can be carried out at a temperature below 100°C. The low temperature of drying may reduce the destruction of heat-sensitive chemicals inside the herbs. The present study aimed at analyzing the drying rate constant of sambiloto leaves during lowpressure drying. Sambiloto leaves were dried at varied temperature of 30°C, 40°C, and 50°C, and varied pressure of 61 kPa, 48 kPa, and 35 kPa. The water content of sambiloto leaves was reduced from ± 70% to ± 10%. The change in water content was measured after 10, 20, 30, 60, 90, 120, 150 and 210 minutes, by using thermogravimetry technique. The drying-rate constant was calculated using the equation of thin films. The drying-rate constant was 0.01 – 0.0175 min-1. It was observed that the drying-rate increases as the pressure decreases. To predict the change of water content in sambiloto leaves during low-pressure drying process, an empirical equation for the drying-rate constant as a function of temperature and pressure was derived from theexperimental data, kprediction= 0,00075T0,823P-0,021.